Performance evaluation and comparison of diode clamped multilevel inverter and hybrid inverter based on PD and APOD modulation techniques - N. Susheela; P. Satish Kumar (International Journal of Advances in Applied Sciences, 2019)
The popularity of multilevel inverters have increasing over the years in various applications without use of a transformer and has many benefits. This work presents the performance and comparative analysis of single phase diode clamped multilevel inverter and a hybrid inverter with reduced number of components. As there are some drawbacks of diode clamped multilevel inverter such as requiring higher number of components, PWM control method is complex and capacitor voltage balancing problem, an implementation of hybrid inverter that requires fewer components and less carrier signals when compared to conventional multilevel inverters is discussed. The performance of single phase diode clamped multilevel inverter and hybrid multilevel inverter for seven, nine and eleven levels is performed using phase disposition, alternate phase opposition disposition sinusoidal pulse width modulation techniques. Both the multilevel inverter are implemented for the above mentioned multicarrier based Pulse Width Modulation methods for R and R-L loads.  The total harmonic distortion is evaluated at various modulation indices. The analysis of the multilevel inverters is done by simulation in matlab / simulink environment.